Variables that affect the development of early vocalizations: their relevance to the assessment. - Pérez, Ana; Martínez-Lorca, Manuela; Zabala, Carmen (Revista de Investigación en Logopedia, 2014)
The aim of this study was to determine the early vocal productions before the first word, and to study the influence of extra-linguistic factors (age, gender, primary caregiver, birth order, maternal education level). To this end, a cross-sectional descriptive study has been performed which involved 39 children of both sexes aged between 8 and 15 months of age. The children went to different schools of public and private Childhood Education in the province of Toledo. As a result we have used the "vocalizations" part of Inventory MacArthur-Bates Communicative Development (López-Ornat, Gallego, Gallo, Karousou, Mariscal and Martinez, 2005). The data show that the speech activity in infants between 8 and 15 months of age appear gradually very early confirming the influence of some extralinguistic variables. Prosodic aspects of language are related to the variable sex and educational level of the mother. Birth as an order variable also shows a connection with the development of vocalizations, particular in babies born in first place. As for the observation of communicative and linguistic performance of babies by the primary caregiver, there is an observational bias appearing greater overestimation of vocalizations by caregivers different from the mother.